CuAAC-ensembled 1, 2, 3-triazole-linked isosteres as pharmacophores in drug discovery: review. Issue 10 (4th February 2020) - Rani, Alisha; Singh, Gurjaspreet; Singh, Akshpreet; Maqbool, Ubair; Kaur, Gurpreet; Singh, Jandeep
Abstract : The review lays emphasis on the significance of 1, 2, 3-triazoles synthesized via CuAAC reaction having potential to act as anti-microbial, anti-cancer, anti-viral, anti-inflammatory, anti-tuberculosis, anti-diabetic, and anti-Alzheimer drugs. Abstract : The review lays emphasis on the significance of 1, 2, 3-triazoles synthesized via CuAAC reaction having potential to act as anti-microbial, anti-cancer, anti-viral, anti-inflammatory, anti-tuberculosis, anti-diabetic, and anti-Alzheimer drugs. The importance of click chemistry is due to its 'quicker' methodology that has the capability to create complex and efficient drugs with high yield and purity from simple and cheap starting materials. The activity of different triazolyl compounds was compiled considering MIC, IC50, and EC50 values against different species of microbes. In addition to this, the anti-oxidant property of triazolyl compounds have also been reviewed and discussed.